A kind of moisture-absorbing self-heating light and warm nylon fabric and preparation method thereof

Through the combination of electrospinning technology and nanoparticles, a hygroscopic self-heating light and warm nylon fabric was prepared, which solved the problem of poor hygroscopicity of nylon fiber fabric, achieved the improvement of water absorption and breathability of the fabric, and improved the movement of Comfort and warmth.

CN119221176BActive Publication Date: 2025-02-25GUANGDONG GUANGWEI KNITTING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411748541.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The existing nylon fiber fabrics have poor hygroscopicity, which leads to the inability to quickly discharge sweat during exercise, especially during high-intensity exercise, affecting the wearer's comfort.

Method used

Electrospinning technology is used to spin composite polymer spinning liquid and polyamide spinning liquid into fiber wires, and hygroscopic self-heating light and warm nylon fabric is prepared by combining specific textile structures and nanoparticles. The fabric further improves water absorption and breathability through alternate treatment of hot and cold and directional freezing.

Benefits of technology

It achieves the ability to provide good moisture absorption and self-heating effect while retaining the characteristics of lightweight fabrics, improving the water absorption and breathability of the fabrics, thereby maintaining comfort during exercise and providing effective warmth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221176B_ABST
    Figure CN119221176B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of fabric preparation, and provides a hygroscopic self-heating light and warm nylon fabric and a preparation method thereof. By configuring a polyamide spinning solution and a composite polymer spinning solution, a polymer with hygroscopic properties is combined with nanoparticles, so that the hygroscopic and heat-generating properties of the nanoparticles interact with the hygroscopic properties of the polymer matrix, and the polyamide spinning solution and the composite polymer spinning solution are spun to form polyamide fiber yarns and composite fiber yarns. Among them, the polyamide fiber yarns are used as warp yarns and the composite fiber yarns are used as weft yarns for weaving to form a hygroscopic self-heating light and warm nylon fabric containing nanoparticles. The prepared hygroscopic self-heating light and warm nylon fabric can provide good hygroscopic and self-heating effects while retaining the characteristics of a lightweight fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric preparation, and in particular to a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric and a preparation method thereof. Background Art

[0002] At present, modern people pay more attention to sports and outdoor activities, and have higher and higher requirements for the comfort and performance of clothing. Therefore, modern people have higher requirements for clothing that pays equal attention to appearance and function. As a result, sports outdoor clothing and winter warm clothing not only provide functionality, but also need to focus on fashion design, so that the wearer can feel confident and comfortable during activities.

[0003] The cotton yarn materials used in sportswear have good air permeability and strong moisture absorption, but poor quick-drying properties. This means that during exercise, cotton yarn clothing easily absorbs sweat and remains damp, which may cause the wearer to feel uncomfortable or increase the difficulty of regulating body temperature. In addition, since it does not have good thermal insulation performance, its thermal insulation performance may not be sufficient to meet the wearer's needs in some high-intensity sports, especially long-term or high-intensity sports.

[0004] At present, nylon fiber fabric is a common choice when preparing sports warm clothing, because nylon fiber can provide excellent warming effect through different textile structures and processing methods. For example, you can choose to use air layer technology or a fabric structure with good warming performance to ensure that body temperature is maintained in a cold environment. It makes the clothing lighter and more breathable, while maintaining sufficient warming performance, allowing the wearer to feel comfortable during exercise without excessive clothing resistance or burden. However, due to the poor hygroscopicity of nylon fiber itself, it cannot effectively absorb sweat from the body surface. This results in the inability to quickly discharge sweat during exercise, especially in high-intensity exercise, affecting the wearer's comfort. Summary of the invention

[0005] The technical problem to be solved by the present invention is that due to the poor hygroscopicity of the existing nylon fiber itself, sweat cannot be discharged quickly during exercise, especially in high-intensity exercise, which affects the comfort of the wearer.

[0006] To this end, the first aspect of the present invention mentions a method for preparing a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric, comprising:

[0007] Step S100: preparing a composite polymer spinning solution and a polyamide spinning solution respectively;

[0008] Step S111: dissolving the hygroscopic polymer in deionized water to prepare a polymer solution;

[0009] Step S112: After subjecting the polymer solution to alternating hot and cold treatments, a salt solution is added to form a salinized polymer solution;

[0010] Step S113: dispersing the nanoparticles in a solvent, and uniformly dispersing the nanoparticles by ultrasonic treatment to obtain a nanoparticle dispersion;

[0011] Step S114: adding the nanoparticle dispersion into the salted polymer solution to make the nanoparticles evenly distributed in the salted polymer solution to obtain a composite polymer spinning solution;

[0012] Step S121: heating and melting the polymerized nylon resin into a liquid state to obtain a polyamide spinning solution;

[0013] Step S200: Spinning the polyamide spinning solution and the composite polymer spinning solution respectively by using electrospinning technology to obtain polyamide fiber filaments and composite fiber filaments;

[0014] Step S300: Weaving the polyamide fiber yarn as the warp yarn and the composite fiber yarn as the weft yarn to produce a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric containing nanoparticles.

[0015] Furthermore, step S120 is: treating the polymer solution at temperatures of 0-10° C., 40-70° C., and 0-10° C. in sequence, and then adding a salt solution to form a salinized polymer solution.

[0016] Furthermore, the hygroscopic polymer is at least one of sodium polyacrylate, polyvinyl alcohol, N-isopropylacrylamide, polyethylene glycol, sodium carboxymethylcellulose, and cellulose derivatives.

[0017] Furthermore, the nanoparticles are at least one of calcium phosphate nanoparticles, calcium oxide nanoparticles, silicon dioxide nanoparticles, iron oxide nanoparticles, zinc oxide nanoparticles, hydroxyapatite nanoparticles, and metal nanoparticles.

[0018] Further, the method comprises: Step S400: using a directional freezing method to treat the moisture-absorbing, self-heating, light, thin, and warm nylon fabric.

[0019] Furthermore, the components of the salt solution include at least one of CaCl2, LiCl, and NaCl.

[0020] Furthermore, in step S140, the nanoparticle dispersion and the salted polymer solution are mixed by a high-pressure homogenizer, and the pressure is controlled to be 20-200 MPa, so that the nanoparticles are evenly distributed in the polymer solution to obtain a composite polymer spinning solution.

[0021] Furthermore, the nanoparticles are plate-shaped nanoparticles or tubular nanoparticles.

[0022] The second aspect of the present application mentions a hygroscopic, self-heating, light, thin, and warm nylon fabric, which is prepared using the preparation method of the hygroscopic, self-heating, light, thin, and warm nylon fabric as described in the first aspect.

[0023] Furthermore, in the moisture-absorbing, self-heating, light, and warm nylon fabric, a receiving space is formed between the warp yarns and the weft yarns, and the receiving space is used to receive air.

[0024] The present invention provides a hygroscopic self-heating light and thin warm nylon fabric and a preparation method thereof, wherein the method comprises: respectively preparing a composite polymer spinning solution and a polyamide spinning solution, firstly, preparing a hygroscopic polymer into a polymer solution and then subjecting it to a cold and hot alternating treatment, adding a salt solution, and adding a nanoparticle dispersion into the salted polymer solution, so that the nanoparticles are evenly distributed in the polymer solution, and obtaining a composite polymer spinning solution; heating and melting the polymerized nylon resin into a liquid state, and obtaining a polyamide spinning solution; and respectively spinning the polyamide spinning solution and the composite polymer spinning solution into polyamide fiber yarns and composite fiber yarns. Among them, the polyamide fiber yarns are used as warp yarns and the composite fiber yarns are used as weft yarns, and the hygroscopic self-heating light and thin warm nylon fabric containing nanoparticles is woven. It can provide a good hygroscopic self-heating effect while retaining the characteristics of a lightweight fabric. Specifically, by combining a polymer with hygroscopic properties with nanoparticles, the hygroscopic heat-generating properties of the nanoparticles interact with the hygroscopic properties of the polymer matrix to generate a hygroscopic self-heating material, thereby achieving the hygroscopic heat-generating effect of the overall material. When the composite material is exposed to a humid environment, both the polymer matrix and the nanoparticles will absorb moisture, increasing the overall water content of the material. This application further utilizes a directional freezing method to improve the water absorption and air permeability of the fabric, so that the fabric can still effectively keep warm while ensuring moisture absorption and air permeability, making it lighter and softer, thereby improving the overall wearing experience. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to make the contents of the present invention more clearly understood, the present invention is further described in detail below based on the specifics of the present invention and in conjunction with the accompanying drawings.

[0026] Figure 1 This is a flow chart of a method for preparing a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric mentioned in the present invention;

[0027] Figure 2 This is a comparison chart of the moisture absorption performance of a method for preparing a moisture-absorbing, self-heating, light, warm nylon fabric mentioned in the present invention. DETAILED DESCRIPTION

[0028] The present invention will be further described below in conjunction with the accompanying drawings and details so that those skilled in the art can better understand the present invention and implement it, but the examples are not intended to limit the present invention.

[0029] refer to Figure 1 The first aspect of the present invention relates to a method for preparing a moisture-absorbing, self-heating, light, thin, and warm nylon fabric, comprising:

[0030] Step S100: preparing a composite polymer spinning solution and a polyamide spinning solution respectively;

[0031] Step S111: dissolving a hygroscopic polymer in deionized water to prepare a polymer solution; in the present technical solution, the hygroscopic polymer is at least one of sodium polyacrylate, polyvinyl alcohol, N-isopropylacrylamide, polyethylene glycol, sodium carboxymethyl cellulose, and a cellulose derivative.

[0032] It should be noted that, first of all, it is necessary to select a suitable hygroscopic polymer. The hygroscopic polymer mentioned in the present application is a water-containing group or other hydrophilic group, such as a carboxyl group, a hydroxyl group, etc. The nanoparticles are flaky nanoparticles or tubular nanoparticles. Due to the unique geometric structure of the flaky nanoparticles or tubular nanoparticles, more water adsorption sites or faster mass transfer paths can be provided.

[0033] The hygroscopic polymer is dissolved in deionized water according to a preset ratio. During the dissolution process, it is fully stirred and heated at the same time to ensure that the polymer is evenly dispersed and dissolved in the water. After the polymer solution of the preset concentration is completed, the pH value of the polymer solution is adjusted to 8-12.

[0034] Step S112: After subjecting the polymer solution to alternating hot and cold treatment, a salt solution is added to form a salinized polymer solution, wherein the ratio of polymer to salt is (2-5):1; it should be noted that the purpose of subjecting the polymer solution to alternating hot and cold treatment is to change the conformation and interaction of the polymer chains, which may lead to changes in the aggregation state in the polymer solution.

[0035] In the technical scheme, the polymer solution is placed under the conditions of 0-10°C, 40-70°C, and 0-10°C in sequence, and then a salt solution is added to form a salinized polymer solution. Exemplarily, the polymer solution is controlled to rise slowly and the temperature is ensured to be 0-10°C for 15-30 min, then the temperature is raised to 40-70°C for 25-40 min, and then the temperature of the polymer solution is controlled to rise to 0-10°C and the reaction is stopped after 15-30 min. The alternating cold and hot treatment can rearrange the polymer molecular chains in the polymer solution, and establish an interconnected polymer hydrogel network through intermolecular hydrogen bonding.

[0036] In this technical solution, after the hot and cold alternating treatment is repeated four times, the polymer solution is added to the salt solution to form a salinized polymer solution; when the salt solution is added to the polymer solution, the salt ions can shield the charges on the polymer chains, thereby changing the interactions between the chains. Specifically, the purpose is to allow the salt ions to fully penetrate into the polymer molecular chain network and add more water absorption sites to the polymer chains.

[0037] Step S113: Disperse the nanoparticles in the solvent, and evenly disperse the nanoparticles by ultrasonic treatment to obtain a nanoparticle dispersion; slowly add the nanoparticles to the solvent, and evenly stir them by means of a stirrer, etc., to ensure that the nanoparticles begin to disperse in the solvent. Then add an appropriate amount of initiator to the mixture of nanoparticles and solvent. Place the mixed solution in an ultrasonic bath, and the nanoparticles are subjected to mechanical force by the action of ultrasonic waves, thereby promoting the nanoparticles to be more evenly dispersed in the solvent. Ultrasonic treatment helps to break the aggregation state between the nanoparticles and improve the dispersion performance.

[0038] It should be noted that the initiators mentioned in the present application are polyethylene glycol and sodium dodecyl sulfate, which can be used for surface modification and dispersion of nanoparticles to improve the dispersibility and stability of nanoparticles.

[0039] Step S114: Add the nanoparticle dispersion to the salted polymer solution and stir to make the nanoparticles evenly distributed in the salted polymer solution to obtain a composite polymer spinning solution; slowly add the prepared nanoparticle dispersion to the salted polymer solution. In order to avoid excessive local concentration, the nanoparticle dispersion can be added dropwise while gently stirring. Exemplarily, a magnetic stirrer or a mechanical stirrer can be used to stir the mixture. The purpose of stirring is to make the nanoparticles evenly distributed in the salted polymer solution. And the stirring speed should be controlled to be moderate to prevent the nanoparticles from agglomerating or settling.

[0040] In this technical solution, if there is still a problem of uneven distribution of nanoparticles after stirring, ultrasonic treatment can be performed again. The mixed solution is placed in an ultrasonic bath to further break up any possible nanoparticle aggregates. This step can improve the uniform distribution of nanoparticles in the polymer solution. The uniform distribution of nanoparticles ensures uniform and stable heat release of the composite material during moisture absorption through interaction with the polymer matrix.

[0041] In the present technical solution, the nanoparticles are at least one of calcium phosphate nanoparticles, calcium oxide nanoparticles, silicon dioxide nanoparticles, iron oxide nanoparticles, zinc oxide nanoparticles, hydroxyapatite nanoparticles, and metal nanoparticles.

[0042] In this technical solution, the nanoparticle dispersion and the salted polymer solution are mixed and stirred by a high-pressure homogenizer to make the nanoparticles evenly distributed in the polymer solution to obtain a composite polymer spinning solution; the nanoparticles and the polymer solution are mixed by a high-pressure homogenizer. Under high pressure, the mixture passes through a narrow channel, and the high shear force and turbulence effect help to evenly disperse the nanoparticles. The reaction under high temperature and high pressure can achieve precise control of the pore size, so that the pore size of the nanoparticles is evenly distributed. Nanoparticles with uniform pore size distribution and high porosity will show a faster moisture absorption rate.

[0043] In the present technical solution, the pressure range of the high-pressure treatment of the nanoparticles is controlled between 20 MPa and 200 MPa. When the pressure is lower than 20 MPa, the pore size of the nanoparticles does not change significantly.

[0044] When the pressure is higher than 200 MPa, the surface of the nanoparticles will be damaged or aggregated, resulting in damage to the morphology, size and dispersion of the particles. This will cause irreversible material changes in the composite material, making it impossible to achieve the hygroscopic properties of the nanoparticles.

[0045] The high specific surface area of ​​nanoparticles can provide more adsorption sites and enhance moisture absorption capacity. The high thermal conductivity of nanoparticles allows the heat generated during moisture absorption to be quickly transferred and dissipated, improving the overall heat release efficiency.

[0046] It should be noted that silicon dioxide nanoparticles have a high specific surface area and hygroscopic properties. They also have excellent thermal stability and chemical stability. When combined with hygroscopic polymers, they can retain their hygroscopic properties well.

[0047] Iron oxide nanoparticles have good magnetic and hygroscopic properties. In the case of selecting iron oxide nanoparticles, the present application can control the hygroscopic properties by adjusting the particle size and surface modification.

[0048] Zinc oxide nanoparticles have a high specific surface area and hygroscopic properties, and are suitable for preparing hygroscopic self-heating materials. In addition, zinc oxide nanoparticles also have photocatalytic activity and antibacterial properties. Its composite with hygroscopic polymers can well retain its hygroscopic properties.

[0049] In the present technical solution, the components of the salt solution include at least one of CaCl2, LiCl, and NaCl. It should be noted that there is an interaction between the salt ions and the molecular chains of the polymer, which can form a local cross-linking phenomenon, which is conducive to providing more sites for the attachment of water molecules. The hygroscopic effect of the composite material prepared in the present application is further improved.

[0050] In this technical solution, a directional freezing method is used to treat a hygroscopic, self-heating, light, thin, and warm nylon fabric. For example, the hygroscopic, self-heating, light, thin, and warm nylon fabric prepared by liquid nitrogen treatment can be treated with liquid nitrogen to change the physical structure of the molecular chain in the composite material, providing abundant sites for the attachment and storage of water molecules, promoting the improvement of the hygroscopic performance of the polymer matrix skeleton of the three-dimensional structure, and constructing a directional microchannel structure in the same direction for it, which is beneficial to the transmission of water molecules during the hygroscopic process on the one hand, and beneficial to the conduction of heat on the other hand.

[0051] Step S200: Spinning the polyamide spinning solution and the composite polymer spinning solution respectively by using electrospinning technology to obtain polyamide fiber yarn and composite fiber yarn; the nylon fiber layer has high tensile strength and modulus, and at the same time, the nylon fiber layer is not easy to deform or over-stretch when subjected to force, and maintains structural stability. The nylon fiber layer has good elasticity and can restore its original shape and size to a certain extent.

[0052] Step S300: Weaving the polyamide fiber yarn as the warp yarn and the composite fiber yarn as the weft yarn to produce a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric containing nanoparticles.

[0053] Nanoparticles can form micro-contacts in the fabric, which can effectively block the conduction of heat and provide good thermal insulation performance.

[0054] It should be noted that since the body's movement trajectory is often along the longitudinal direction of the body during most sports and activities, the human body usually generates more longitudinal tensile force and stretching amplitude when moving. Therefore, the elastic properties of the fabric in the warp (longitudinal) direction are crucial to wearing comfort and functionality.

[0055] The present invention uses polyamide fiber yarns with greater elasticity as warp yarns and composite fiber yarns as weft yarns for weaving to produce a moisture-absorbing, self-heating, light, warm nylon fabric containing nanoparticles. It can further improve the fit and comfort of clothing, especially in scenarios that require large-scale body movement or stretching, such as sports, outdoor activities, etc. It can stretch and rebound with the movement of the body, will not restrict movement or comfort, and can also maintain the shape and overall appearance of the clothing.

[0056] It should be noted that, during the spinning process, the obtained hygroscopic self-heating light and thin warm nylon fabric can be adjusted according to the thickness required in actual production. For example, step S300 can be repeated continuously to adjust the thickness of the hygroscopic self-heating light and thin warm nylon fabric. In a feasible implementation, the mechanical properties and hygroscopic self-heating properties of the material can be adjusted by adjusting the number of step S300.

[0057] The technical solution also includes: Step S400: using a directional freezing method to treat the moisture-absorbing, self-heating, light, and warm nylon fabric.

[0058] The hygroscopic, self-heating, light, and warm nylon fabric was placed on a metal rack partially immersed in liquid nitrogen. Through liquid nitrogen treatment, a huge temperature gradient was quickly generated in the same direction, prompting countless ice crystals to grow from bottom to top. After freeze-drying for 24 hours, the surface of the hygroscopic, self-heating, light, and warm nylon fabric was quickly cooled, resulting in a rapid increase in the temperature difference between the surface and the inside. This temperature gradient prompted moisture to crystallize into ice crystals from bottom to top inside the fabric, forming a directional microscopic pore structure during the freezing process, so that many tiny channels were formed inside the fabric, which helped to absorb and conduct moisture more quickly and efficiently, and also increased the specific surface area of ​​the material, which means that the area of ​​contact between the surface of the material and moisture is increased, thereby improving the water absorption capacity. Therefore, during the directional freezing process, the pore structure formed not only improves water absorption, but also creates interconnected channels. These channels allow air to pass through the material more freely, thereby improving air permeability. Although the directional freezing method improves water absorption and air permeability, it also maintains good thermal insulation properties through the optimized pore structure, which means that the material can still effectively keep warm while absorbing moisture and being breathable. It does not significantly increase the weight of the material, but may make it lighter and softer, thereby improving the overall wearing experience.

[0059] The hygroscopic self-heating type thin and warm nylon fabric prepared in the present application has a hygroscopic self-heating effect by combining a polymer with hygroscopic properties with nanoparticles. A hygroscopic polymer, i.e. a polymer with strong hydrophilicity, is used to combine with water molecules through hydrogen bonds or ionic bonds. That is, on the one hand, water molecules are adsorbed on the surface or in the pores of the polymer. On the other hand, water molecules form hydrogen bonds or other weak interaction forces with the hydrophilic groups on the polymer molecular chains to absorb water and release heat.

[0060] The present invention combines nanoparticles with hygroscopic polymers. When the composite material is exposed to a humid environment, both the polymer matrix and the nanoparticles absorb moisture, increasing the overall moisture content of the material. The mechanism by which the nanoparticles and polymers are combined to form a hygroscopic self-heating material is mainly through the interaction between the hygroscopic heat-generating properties of the nanoparticles and the hygroscopic properties of the polymer matrix, thereby achieving the hygroscopic heat-generating effect of the overall material.

[0061] The second aspect of the present application mentions a hygroscopic self-heating light and thin warm nylon fabric, which is prepared by a preparation method of a hygroscopic self-heating light and thin warm nylon fabric as in the first aspect. Exemplarily, air spinning or air layer technology is used to weave a storage space between the warp yarn and the weft yarn, and the storage space is used to accommodate air. This design can help the fabric absorb moisture and promote moisture removal, while also providing appropriate ventilation and air permeability. Therefore, this fabric not only has a warming effect, but also can regulate humidity to a certain extent and improve comfort. The design of this multi-layer structure injects more functionality into the hygroscopic self-heating light and thin warm nylon fabric, so that it has good air permeability and moisture management capabilities while keeping warm. In addition, the hygroscopic self-heating light and thin warm nylon fabric has all the beneficial effects mentioned in the first aspect above, which will not be repeated here.

[0062] The preparation method of a moisture-absorbing, self-heating, lightweight, warm nylon fabric mentioned in the present application will be described below in the form of an embodiment in combination with the accompanying drawings.

[0063] Example 1

[0064] Step S100: preparing a composite polymer spinning solution and a polyamide spinning solution respectively;

[0065] Step S111: dissolving polyvinyl alcohol in deionized water at 80° C. and continuously stirring for 4 h, adjusting the pH to 8, to obtain a polyvinyl alcohol solution;

[0066] Step S112: The polyvinyl alcohol solution is treated by a cold and hot cycle, and its temperature is controlled to 5°C, 60°C, and 5°C in sequence. Each temperature is maintained for 15 minutes and repeated 3 times. Subsequently, the polyvinyl alcohol solution and the LiCl aqueous solution are mixed in a molar ratio of 3:1 and stirred continuously for 6 hours to allow the salt ions to fully penetrate into the polymer chain network;

[0067] Step S113: dispersing zinc oxide nanoparticle powder in deionized water and adding sodium dodecyl sulfate, and uniformly dispersing the nanoparticles by ultrasonic treatment;

[0068] Step S114: adding the zinc oxide nanoparticle dispersion to the PVA-LiCl composite polymer spinning solution through a high-pressure homogenizer, controlling the pressure to 80 MPa, so that the nanoparticles are evenly distributed in the polymer solution to obtain a composite polymer spinning solution; in the composite polymer spinning solution, the molar ratio of PVA-LiCl: zinc oxide nanoparticles is 2:1;

[0069] Step S211: heating and melting the polymerized nylon resin into a liquid state, and then adding a proper amount of NaOH solution into the liquid polymerized nylon resin to prepare a polyamide spinning solution with a concentration of 20%;

[0070] Step S200: using electrospinning technology, injecting the prepared polyamide spinning solution and composite polymer spinning solution into two 8 mL syringes respectively, spinning in an environment of temperature of 10° C. and relative humidity of 20%, to obtain polyamide fiber filaments and composite fiber filaments;

[0071] Step S300: using polyamide fiber yarns as warp yarns and composite fiber yarns as weft yarns to weave and produce a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric containing nanoparticles;

[0072] Step S400: freeze-dry the obtained hygroscopic self-heating light and warm nylon fabric for 24 hours, and then dry it in a blast oven at 60° C. for 12 hours for standby use.

[0073] Example 2

[0074] The difference between Example 2 and Example 1 is that the pH of the polyvinyl alcohol solution obtained is 10, and the remaining reaction conditions are the same as those in Example 1. The similarities can be referenced to each other, and this application will not repeat them here.

[0075] Example 3

[0076] The difference between Example 2 and Example 1 is that the polyvinyl alcohol solution is treated by a cold and hot cycle, and its temperature is controlled to 2° C., 50° C., and 2° C. in sequence. Each temperature is maintained for 15 minutes and repeated 3 times.

[0077] Subsequently, the polyvinyl alcohol solution and the LiCl aqueous solution were mixed at a molar ratio of 4:1 and stirred for 6 hours to allow the salt ions to fully penetrate into the polymer chain network. The remaining reaction conditions were the same as those in Example 1, and the similarities can be referred to each other, and this application will not repeat them here.

[0078] Example 4

[0079] The zinc oxide nanoparticle dispersion is added to the PVA-LiCl composite polymer spinning solution by a high-pressure homogenizer, and the pressure is controlled to be 100 MPa, so that the nanoparticles are evenly distributed in the polymer solution to obtain a composite polymer spinning solution. The rest of the reaction conditions are the same as those in Example 1, and the same parts can be referred to each other, and this application will not repeat them here.

[0080] Comparative Example 1

[0081] Step S100: preparing a polyamide spinning solution, heating and melting the polymerized nylon resin into a liquid state, and then adding a proper amount of NaOH solution into the liquid polymerized nylon resin to prepare a polyamide spinning solution with a concentration of 20%;

[0082] Step S200: using electrospinning technology, injecting the prepared polyamide spinning solution into two 8 mL syringes respectively, spinning in an environment of a temperature of 10° C. and a relative humidity of 20%, to obtain polyamide fiber filaments;

[0083] Step S300: Weaving polyamide fiber yarn to obtain nylon fabric.

[0084] The moisture absorption test was conducted on the fabrics of Examples 1-4 and Comparative Example 1 to explore the influence of moisture absorption performance within 500 minutes. The moisture absorption test was conducted in a constant temperature and humidity chamber at a temperature of 25°C and relative humidity of 25%, 55% and 85% respectively. The weight of the dry fabric was first measured with an analytical balance, and then the sample was placed in a constant temperature and humidity chamber, and the weight after moisture absorption was measured at regular intervals.

[0085] By tracking and recording, after a period of time, when the remaining weight of the sample remains basically unchanged, it is regarded as a sign that the water absorption is complete.

[0086] like Figure 2 As shown, at a relative humidity of 25%, 55% and 85%, the moisture absorption of Example 1, Example 2, Example 3 and Example 4 are 1.25 g / g, 1.24 g / g, 1.25 g / g and 1.26 g / g respectively, and the moisture absorption of Comparative Example 1 is 0.5 g / g. As the relative humidity gradually increases, Example 1, Example 2, Example 3 and Example 4 all show good moisture absorption performance, among which the embodiments of the present application show a moisture absorption of more than 3.8 g / g under a relative humidity of 85%, and can still show good moisture absorption capacity even under lower relative humidity conditions.

[0087] The heat release experiment was conducted on the fabrics of Examples 1-4 and Comparative Example 1, and the experiment was repeated three times to explore the effect of the heat release effect within 30 minutes. The moisture absorption experiment was carried out in a constant temperature and humidity chamber with an initial temperature of 25°C. The temperature changes of the fabrics of Examples 1-4 and Comparative Example 1 during the experiment were recorded within 30 minutes, and the weight after moisture absorption was measured at regular intervals.

[0088] Referring to Table 1, which shows the maximum temperature rise value and the average temperature rise value of the fabric within 30 minutes, it can be seen that when the structural parameters of Examples 1-4 and Comparative Example 1 are the same, the heat generation performance of Examples 1-4 is significantly higher than that of the fabric of Comparative Example 1.

[0089]

[0090] Obviously, the above is only an example for clear explanation and is not a limitation of the implementation method. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.

[0091] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0092] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium; it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0093] In the present invention, unless otherwise clearly specified and limited, when a first feature is “on” or “below” a second feature, it may be that the first and second features are in direct contact, or that the first and second features are in indirect contact through an intermediate medium. Moreover, when a first feature is “above”, “above” or “above” a second feature, it may be that the first feature is directly above or obliquely above the second feature, or it may simply mean that the first feature is higher in level than the second feature. When a first feature is “below”, “below” or “below” a second feature, it may be that the first feature is directly below or obliquely below the second feature, or it may simply mean that the first feature is lower in level than the second feature.

[0094] In the description of this specification, the description of the terms "one", "some", "", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the or example are included in at least one or examples of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different or examples and the features of the different or examples described in this specification without contradiction.

[0095] Although the present invention has been shown and described above, it is to be understood that the above is exemplary and is not to be construed as limiting the present invention. A person skilled in the art may make changes, modifications, substitutions and variations to the above within the scope of the present invention.

Claims

1. A method for preparing a moisture-absorbing, self-heating, light, warm nylon fabric, characterized in that: include: Step S100: preparing a composite polymer spinning solution and a polyamide spinning solution respectively; Step S200: Spinning the polyamide spinning solution and the composite polymer spinning solution respectively by using electrospinning technology to obtain polyamide fiber filaments and composite fiber filaments; Step S300: using polyamide fiber yarns as warp yarns and composite fiber yarns as weft yarns to weave and produce a moisture-absorbing, self-heating, light, thin, warm-keeping nylon fabric containing nanoparticles; Wherein, the step S100 includes: Step S111: dissolving the hygroscopic polymer in deionized water to prepare a polymer solution; Step S112: placing the polymer solution under the conditions of 0-10° C., 40-70° C., and 0-10° C. for alternating hot and cold treatments, and then adding a salt solution to form a salinized polymer solution; Step S113: dispersing the nanoparticles in a solvent, and uniformly dispersing the nanoparticles by ultrasonic treatment to obtain a nanoparticle dispersion; Step S114: mixing the nanoparticle dispersion and the salted polymer solution by a high-pressure homogenizer, controlling the pressure to be 20-200 MPa, so that the nanoparticles are evenly distributed in the salted polymer solution, and obtaining a composite polymer spinning solution; Step S121: heating and melting the polymerized nylon resin into a liquid state to obtain the polyamide spinning solution; The hygroscopic polymer is polyvinyl alcohol; the nanoparticles are zinc oxide nanoparticles; The nanoparticles are sheet-shaped nanoparticles or tubular nanoparticles; the components of the salt solution are selected from at least one of CaCl2, LiCl and NaCl.

2. The method for preparing a moisture-absorbing, self-heating, light, thin, warm nylon fabric according to claim 1, characterized in that: The step S300 further includes: Step S400: using a directional freezing method to treat the moisture-absorbing, self-heating, lightweight, warm-keeping nylon fabric.

3. A hygroscopic, self-heating, light, thin, and warm nylon fabric, prepared by the method for preparing a hygroscopic, self-heating, light, thin, and warm nylon fabric as described in any one of claims 1 to 2.

4. The moisture-absorbing, self-heating, light, warm nylon fabric according to claim 3, characterized in that: In the moisture-absorbing, self-heating, light, and warm nylon fabric, a receiving space is formed between the warp yarns and the weft yarns, and the receiving space is used to receive air.

Citation Information

Patent Citations

  • Heat-storage warm-keeping light nylon fabric and production method thereof

    CN117604701A

  • Preparation method and application of temperature-sensitive super absorbent fiber

    CN117626462A

  • Stable aqueous polymer dispersions and a process for their preparation

    CN1325417A